PENERAPAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN LUKA BERAT DI PENGADILAN NEGERI SAMARINDA - Muhammad Mariadi (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTIONMaltreatment is a form of action that can harm other people, namely towards physicality. One of them is that it can cause serious injury or can even cause the loss of a person's life. These actions occur due to factors including uncontrolled community behavior due to low levels of education and environmental influences, poor association which ultimately results in disputes both personal and group. The problem raised in this study is how the application of criminal law to criminal acts of maltreatment that resulted in serious injuries in district court Samarinda and what is the legal consideration of judges in making decisions on crimes of persecution that resulted in serious injuries in district court Samarinda.The type of research used is normative juridical research, library research with the problem approach used in the writing of this thesis is the statute approach.The results showed that the application of criminal law in the case No.223 / Pid.B / PN.Smr was correct because the defendant's actions more fulfilled the elements of Article 351 paragraph (2) of the Criminal Code. And the legal considerations of the judge in making a verdict in criminal case No.223 / Pid.B / PN.Smr with three valid evidence, namely the victim's witness statement, the proof of the Visum at repertum and the statement of the defendant And the kayin judge because of it.Keywords: Law Application, Crime of Persecution, Serious Injury